2010
DOI: 10.1016/j.jcv.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of viral load of respiratory pathogens and co-infections with disease severity in children hospitalized for lower respiratory tract infection

Abstract: Specific viral single and co-infections as well as viral load contribute to disease severity in children with LRTIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
191
7
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(236 citation statements)
references
References 33 publications
28
191
7
10
Order By: Relevance
“…The HRV+RSV coinfection predominance could reflect the high frequency of these 2 infections in children with ARIs, which was also reported by others, 7,9,11,13,25 and the overlap in time periods when occurrence of respiratory infections caused by both viruses was high, from February to June. 27 We had shown previously that coinfection with HRV and another respiratory virus was not associated with disease severity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The HRV+RSV coinfection predominance could reflect the high frequency of these 2 infections in children with ARIs, which was also reported by others, 7,9,11,13,25 and the overlap in time periods when occurrence of respiratory infections caused by both viruses was high, from February to June. 27 We had shown previously that coinfection with HRV and another respiratory virus was not associated with disease severity.…”
Section: Discussionsupporting
confidence: 76%
“…12 Underlying risk conditions may also be involved in disease severity. 9,13 Again, the reports are contradicting; atopic family history has been associated with severe HRV infection, whereas exposure to smoking has not, 11 and the opposite has been reported in another study. 9 Furthermore, congenital heart disease was considered a risk factor in 1 study 3 but not in another.…”
Section: What This Study Addsmentioning
confidence: 91%
“…38,39 Finally, the qPCR method used in our study was not appropriate to adequately assess viral load, which has been found to be associated with severity of disease. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of acute respiratory tract infection (ARI) and discrimination between bacterial and viral infection is not straight-forward. The diagnosis, clinical management, and understanding of the pathogenesis of a child presenting with symptoms of viral infection can be readily improved by using multiplex PCR to determine the presence or absence of a viral respiratory pathogen (3,4).…”
Section: Introductionmentioning
confidence: 99%